Microeconomic theory : - Nicholson, Walter (Dryden Press, 1998)
Stressing both intuition and analytical precision, this classic text uses a calculus-based approach to present complete, up-to-date coverage of all key microeconomic topics. The seventh edition is suitable for use in a more rigorous first intermediate microeconomics course or in a first-year graduate course.